2020
DOI: 10.1038/s41598-020-61881-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, fluorescence tagging and gene-expression study of CuInS/ZnS QDS - meso (hydroxyphenyl) porphyrin conjugate against human monocytic leukemia cells

Abstract: The toxicity of heavy metals present in binary semiconductor nanoparticles also known as quantum dots (QDs) has hindered their wide applications hence the advent of non-toxic ternary quantum dots. These new group of quantum dots have been shown to possess some therapeutic action against cancer cell lines but not significant enough to be referred to as an ideal therapeutic agent. In this report, we address this problem by conjugating red emitting CuInS/ZnS QDs to a 5,10,15,20-tetrakis(3hydroxyphenyl)porphyrin-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…Therefore, growing efforts are devoted to the development of biocompatible and toxic heavy metal-free QDs. [7][8][9][10][11] Among them, ternary I-III-VI chalcopyrite-type materials are becoming the focus of interest. [12][13][14] These ternary QDs, regarded as promising eco-friendly materials for multiple applications, display a direct band gap (1.04-1.87 eV in the bulk materials) and high absorption coefficients (10 4 -10 5 cm -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, growing efforts are devoted to the development of biocompatible and toxic heavy metal-free QDs. [7][8][9][10][11] Among them, ternary I-III-VI chalcopyrite-type materials are becoming the focus of interest. [12][13][14] These ternary QDs, regarded as promising eco-friendly materials for multiple applications, display a direct band gap (1.04-1.87 eV in the bulk materials) and high absorption coefficients (10 4 -10 5 cm -1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the search for alternative methods is imperative. QDs with desired properties can be achieved by the varying the composition, ratio of the metal precursors, capping agent/stabilizers, type of stabilizers/capping agent, synthesis temperature, post-synthetic modification and passivation shells [8,18,[19][20][21][22]28,32,38,40,44]. Table 1.…”
Section: Synthetic Strategies For Cis Qdsmentioning
confidence: 99%
“…Proper control over composition can lead to the formation of a different crystal structure (cubic to wurtzite structure) [28][29][30][31]. Several reports have been published on the synthesis of CIS NCs such as synthesis in solid phase [32,33], hydrothermal (including pressure cooker) [18,[34][35][36][37], decomposition of single-source precursors [28,[38][39][40][41] and the hot injection [42][43][44][45] method (Table 1). Hirpo et al [46] reported the conversion of (Ph 3 P) 2 CuIn(SEt) 4 and (Ph 3 P) 2 CuIn(SBu) 4 to CIS NCs.…”
Section: Synthetic Strategies For Cis Qdsmentioning
confidence: 99%
See 2 more Smart Citations